PERSONALISASI PEMBELAJARAN FIQH BERBASIS GENERATIVE AI: TRANSFORMASI PERAN GURU DALAM RUANG KELAS DIGITAL 5.0. - Ilyas Rozak Hanafi; Hasbullah Hasbullah; Muhammad Yasin; Susanto Susanto; Muhamad Qomarudinul Huda; Ninik Muhajiroh (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT Entering the Society 5.0 era, the integration of artificial intelligence in education has become an essential necessity, including in Islamic Religious Education learning. However, the utilization of Generative Artificial Intelligence (Gen-AI) in Fiqh learning remains limited to technical aspects, while pedagogical dimensions, ethical considerations, and the transformation of teachers’ roles have not been extensively explored. This study aims to examine the personalization of Gen-AI-based Fiqh learning and analyze the transformation of teachers’ roles within the Digital 5.0 classroom environment. The research employed a qualitative approach using a library research method through philosophical-pedagogical content analysis of relevant literature. The findings indicate that Gen-AI enables adaptive, differentiated, and contextual Fiqh learning through personalized materials, digital tutors, case simulations, and individualized feedback tailored to students’ needs. The Digital 5.0 classroom also introduces prompt pedagogy as a new competency in AI-assisted learning interactions, accompanied by the risk of AI hallucination that requires teacher validation. Other findings reveal the transformation of teachers into digital curators, sharia validators, reflective facilitators, and moral compasses. In conclusion, Gen-AI integration does not replace teachers’ roles but strengthens pedagogical, spiritual, and character-building functions in Fiqh learning within the Society 5.0 era. ABSTRAK Memasuki era Masyarakat 5.0, integrasi kecerdasan buatan dalam pendidikan menjadi kebutuhan penting, termasuk dalam pembelajaran Pendidikan Agama Islam. Namun, pemanfaatan Generative Artificial Intelligence (Gen-AI) dalam pembelajaran Fiqh masih terbatas pada aspek teknis, sementara dimensi pedagogis dan transformasi peran guru belum banyak dikaji. Penelitian ini bertujuan untuk mengeksplorasi personalisasi pembelajaran Fiqh berbasis Gen-AI serta menganalisis transformasi peran guru dalam ruang kelas digital 5.0. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kepustakaan (library research) melalui analisis konten filosofis-pedagogis. Hasil penelitian menunjukkan bahwa Gen-AI memungkinkan pembelajaran Fiqh yang adaptif, diferensiatif, dan kontekstual melalui personalisasi materi, tutor digital, simulasi kasus, dan umpan balik individual. Ruang kelas digital 5.0 juga melahirkan pedagogi prompt sebagai keterampilan baru dalam interaksi belajar berbasis AI, namun disertai risiko AI hallucination yang menuntut validasi guru. Temuan lainnya menunjukkan transformasi peran guru menjadi kurator digital, validator syar’i, dan kompas moral. Kesimpulannya, integrasi Gen-AI tidak menggantikan peran guru, tetapi memperkuat fungsi pedagogis dan spiritual dalam pembelajaran Fiqh di era digital 5.0.